(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
Students with learning disabilities are identified by cognitive tests and special educational tools to assess learning ability. The connection between cognitive ability and learning disability is assumed. The identification of a learning disorder is based on the detection of cognitive and ability deficits. The aim of the presented research is to explore the theory guiding the investigation. In our country, education of children with learning disabilities is integrated. However, a problem may be that inclusive education and a deficit-oriented traditional view are not compatible. Research has shown that cognitive deficits alone do not imply learning deficits. A conceptual distinction cannot be made directly in terms of learning disability and based on measurement results. Research into the background of learning disability has also shown that diagnostics cannot always be linked to test results in the practice under investigation. Several deficit-oriented views and attitudes can be identified in the domestic education system. Qualitative research of expert opinions summarizing the test results may reveal the relevant variables and the theory driving the categorization. Practice and available theories can then be compared. This can answer the question of the relevance of identifying and categorising learning disabilities in an inclusive education model.